Measurement and Theory of Resonance Raman Optical Activity for Gases, Liquids, and Aggregates. What It Tells about Molecules - Zając, Grzegorz; Bouř, Petr (The journal of physical chemistry. B, 2022)
Resonance Raman Optical Activity (RROA) appeared as a natural extension of the nonresonance branch. It combines the structural sensitivity of chiroptical spectroscopy with the signal enhancement coming from the resonance of molecular electronic transitions with the excitation laser light. However, the idea has been hampered by many technical and theoretical problems that are being clarified only in recent years. We provide the theoretical basis and several examples documenting the problems, achievements, and potential of RROA, in particular in biomolecular studies.
Keywords: vibrace; Optical Rotation; světlo; plyny; optická otáčivost; Spectrum Analysis, Raman; Vibration; Light; Ramanova spektroskopie; Gases